Sex- and gender-sensitive public health research: an analysis of research proposals in a research institute in the Netherlands. Issue 1 (2nd January 2021) - van Hagen, Lisanne Jeannine; Muntinga, Maaike; Appelman, Yolande; Verdonk, Petra
ABSTRACT: Taking sex and gender into account in public health research is essential to optimize methodological procedures, bridge the gender gap in public health knowledge, and advance gender equality. The aim of this study was to evaluate the current status of sex and gender considerations in public health research proposals in a Dutch research institute. We screened a random sample of 38 proposals submitted for review to the institute's science committee between 2011 and 2016. Using the Canadian Institutes of Health Research' Gender and Health Institute criteria for gender-sensitive research and qualitative content analysis, we assessed if, and how sex and gender were considered throughout the proposals (background, research aim, design, data collection, and analysis). Our results show that in general, both sex and gender were poorly considered. Gender was insufficiently taken into account throughout most proposals. When sex was mentioned in a proposal, its consideration was often inconsistent and fragmented. Finally, we identified common methodological pitfalls. We recommend that public health curricula and funding bodies increase their focus on implementing sex and gender in public health research, for instance through quality criteria, training programs for researchers and reviewers, and capacity building initiatives.